Complete unknown [videorecording (DVD)] - Marston, Joshua; Weisz, Rachel, 1970-; Shannon, Michael, 1974-; Glover, Danny; Bates, Kathy, 1948- (Great Point Media, 2016)
Complete unknown is Marston's first English language film and centers on Tom and a mysterious woman named Alice. When Tom and his wife host a dinner party to celebrate his birthday, one of their guests brings a date named Alice. Tom is convinced he knows her even though she's going by a different name with a different biography, and she's not acknowledging she knows him.